Analysis of Energy Loss through Conventional Refractory Lining in Refinery Heater and its Conservation Measures - Prasanth, R; Muralidharan, M; Arun, A; Ravi Shankar, S; Vinoth, S; Vinod Kumar, Y (International Journal of Engineering and Technology, 2018)
The work of this project is to analyze theinsulation materials currently used in the furnace of CPCL refinery which is a crude distillation unit heater to minimize the heat loss through the radiant wall section by substituting them with advanced insulating materials.There are some advanced materials whose properties are well suited for the insulation purpose in the furnace wall which could apparently reduce the heat loss through the walls. The general properties which include weight, thickness, thermal conductivity, are calculated to prove that these materials can be used as a replacement to those of the regular insulation materials.The materials which have been taken for analysis can reduce heat loss and improve thermal efficiency it will not require much maintenance activities compared to the old insulation and installing the new insulation is much easier than old as it can be handled easily.This paper will prove that replaced materials will act as an effective insulation than old type.Â